2019
DOI: 10.1186/s12913-019-3911-x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain after cesarean section: assessment and management in a tertiary hospital in a low-income country

Abstract: BackgroundThere is little information about the current management of pain after obstetric surgery at Mulago hospital in Uganda, one of the largest hospitals in Africa with approximately 32,000 deliveries per year. The primary goal of this study was to assess the severity of post cesarean section pain. Secondary objectives were to identify analgesic medications used to control post cesarean section pain and resultant patient satisfaction.MethodsWe prospectively followed 333 women who underwent cesarean section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
38
4
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 10 publications
8
38
4
5
Order By: Relevance
“…In this study, the pain was signi cantly reduced in TAP group as compared to control group with statistical signi cance at 0, 6, 12, 24 hours when assessed during movement on bed including sitting, sleeping and deep breath. This was similar to study done in India and Islamabad-Pakistan which involved 60 participants, whereby TAP block showed less pain during movement resulted in earlier readiness for discharge, early ambulation, early resumption of bowel activity and was statistically signi cant with (p value=0.046) [15] [9] In Uganda RCT study comparing intrathecal morphine and TAP block showed the mean numerical rating score for intrathecal morphine vs. transversus abdominis plane blocks at 8 h,16hr and 24hr was signi cantly reduced for movement and cough in transversus abdominis plane blocks different from this study at 24hrs [16].In this study it was not statistically signi cant at all time when cough pain score was high on both groups. This could be because the pain of cesarean section essentially described into acute moderate to severe, has basically two components somatic (from abdominal wall incision) and visceral (from the uterus) which TAP act on somatic [14].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the pain was signi cantly reduced in TAP group as compared to control group with statistical signi cance at 0, 6, 12, 24 hours when assessed during movement on bed including sitting, sleeping and deep breath. This was similar to study done in India and Islamabad-Pakistan which involved 60 participants, whereby TAP block showed less pain during movement resulted in earlier readiness for discharge, early ambulation, early resumption of bowel activity and was statistically signi cant with (p value=0.046) [15] [9] In Uganda RCT study comparing intrathecal morphine and TAP block showed the mean numerical rating score for intrathecal morphine vs. transversus abdominis plane blocks at 8 h,16hr and 24hr was signi cantly reduced for movement and cough in transversus abdominis plane blocks different from this study at 24hrs [16].In this study it was not statistically signi cant at all time when cough pain score was high on both groups. This could be because the pain of cesarean section essentially described into acute moderate to severe, has basically two components somatic (from abdominal wall incision) and visceral (from the uterus) which TAP act on somatic [14].…”
Section: Discussionsupporting
confidence: 86%
“…The variations could be explained by larger and multicenter sample size and better practice on pain management in the developed United States of America. Another prospective survey in Uganda reported that the incidence of severe acute pain after CS at three time-points at Zero, 6 th and 24 th hr since surgery was 33%, 39% and 29% respectively [25]. In-contrast, the incidence of postoperative pain was much higher in our study at all time-points (2 nd , 12 th , and 24 th hr).…”
Section: Discussioncontrasting
confidence: 71%
“…The 4-to 6-h time interval was chosen to capture the worst pain after cesarean section as well as the peak effect of the quadratus lumborum block. 18 The 24-h time interval was chosen for oral morphine equivalent consumption because it potentially captures the maximal duration of the intervention examined (i.e., quadratus lumborum block).…”
Section: Primary and Secondary Outcomesmentioning
confidence: 99%